2004
DOI: 10.1002/bjs.4504
|View full text |Cite
|
Sign up to set email alerts
|

Tumour morphology as a predictor of outcome after local excision of rectal cancer

Abstract: Morphology is a clinical guide to prognosis after local excision. Non-exophytic cancers are associated with high-risk histopathological features that render tumours of this type unsuitable for local excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
(15 reference statements)
0
17
0
Order By: Relevance
“…According to many studies, well-or moderated-differentiated cancers with invasion limited to the most superficial part of the submucosa, and no lymphovascular invasion have very low probability of nodal metastases and can be treated locally, while radical resection should be offered if adverse features are present [3,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…According to many studies, well-or moderated-differentiated cancers with invasion limited to the most superficial part of the submucosa, and no lymphovascular invasion have very low probability of nodal metastases and can be treated locally, while radical resection should be offered if adverse features are present [3,[40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors report that ulceration (nonexophytic) is an unfavorable criteria for local excision. 33,40,41 Brodsky et al 33 reported an increased incidence of lymph node metastasis for ulcerated tumors (24 vs. 11 percent, P = 0.06). In a recent study, the global survival and local recurrence rates were respectively better for nonulcerated tumors (90 and 9 percent) than for ulcerated tumors (49 and 40 percent).…”
Section: Clinical and Pathologic Criteriamentioning
confidence: 95%
“…In a recent study, the global survival and local recurrence rates were respectively better for nonulcerated tumors (90 and 9 percent) than for ulcerated tumors (49 and 40 percent). 40 Depth of Wall Invasion. Depth of wall invasion or T stage is critical in patient selection because it provides the best estimate of the probability of regional lymph node metastasis.…”
Section: Clinical and Pathologic Criteriamentioning
confidence: 99%
“…Risk of lymph nodes involvement is 0-12% for T1 cancer and 12-28% for T2 cancers (Sengupta & Tjandra, 2001). Features associated with a significantly increased risk of lymph node metastases include poor differentiation, lymphovascular invasion and size greater than 3cm (Chambers et al, 2004;Nascimbeni et al, 2002).…”
Section: Tarmentioning
confidence: 99%